Gastronomy Tourism Growth in Malaysia: A Case Study of Malay Restaurants Performance in Klang Valley - Raja Abdullah, Raja Puteri Saadiah; Isa, Siti Suriawati (Journal of Tourism and Hospitality Education, 2020)
Today one of the most popular niche tourism markets is gastronomy tourism. The popularity of gastronomy tourism is also called as soft power approaches by some tourism scholars. This niche market is part of cultural and ecotourism market. Malaysia is recognized as a multi-ethnic and multi cultural country that includes countless ethnics such as Malay, Chinese, Indian and others. Although Malay leads the major ethnics in Malaysia, Malay restaurant less likely can stay longer in the industry. There are several factors from previous cases involve in Malay restaurants that result to this ethnic’s restaurant fail to survive. Since Malaysia is a multi-ethnic country the food in Malaysia have combination from all ethnics and unique in its own way. Each state in Malaysia has their own dishes and some dishes may diff er from another state. Since Malay or Bumi putra ethnic comprises the biggest ethnic in Malaysia with more than half of the country’s population, the objective of this study was to analyze the internal factors affecting business growth performance in Malay ethnic restaurant. Survey questionnaires were distributed to selected Malay restaurants to find out about their growth rate performance.